Lockdowns as options - Sweder J.G. van Wijnbergen (Tinbergen Institute, 2021)
I show that the irreversibility of dying coupled with gradual information acquisition over time on the likely arrival and eventual effectiveness of vaccines confers a real option value to lockdown strategies that delay the incidence of a pandemic.The case for lockdown strategies becomes stronger the more likely vaccine discovery is, and the less uncertainty exists about its effectiveness.
Keywords: G12; G13; G18; 330; Pandemic Dynamics; Stochastic Vaccine arrival; information acquisition; irreversibility; lockdowns; real options